Effects of NO2 and Ozone on Pollen Allergenicity - Frank, Ulrike; Ernst, Dieter (Frontiers in Plant Science, 2016)
This mini-review summarizes the available data of the air pollutants NO2 and ozone on allergenic pollen from different plant species, focusing on potentially allergenic components of the pollen, such as allergen content, protein release, IgE-binding or protein modification. Various in vivo and in vitro studies on allergenic pollen are shown and discussed.